Art 20 (Thames & Hudson, 2005)
"Multimedia encyclopedia featuring over 3500 images, audios of artists' voices, videos of kinetic and video art and more than 2500 entries of artists, movements, galleries, collectors and critics". - Περίληψη από το κιβώτιο